Coffee Development Model Based On Circular Economy - Djazuli, Raden Achmad; Tanjung, Garist Sekar (JURNAL AGRIBISAINS, 2025)
This research examines the implementation of circular economy principles in the coffee agribusiness value chain in Bangka Belitung Province. The urgency of this research is driven by the significant volume of coffee waste (approximately 714 tons annually in Bangka Belitung) that threatens environmental sustainability and represents lost economic opportunities. Using a qualitative approach with case study methods, the study identifies strategies for processing coffee waste into value-added products. The results show that utilizing coffee waste can potentially increase farmers' income by up to 35% and reduce organic waste by 60%. The development model based on pentahelix collaboration (farmers, industry, academia, government, and community) is key to successful implementation of circular economy. The research recommends integrating circular economy principles into regional agricultural development policies, strengthening farmers' institutional capacity, and developing appropriate technology for coffee waste utilization. This research offers new insights into creating sustainable agricultural systems through waste management innovation and multi-stakeholder collaboration, addressing the critical gap in circular economy implementation in regional coffee industries.